Initial Amino Acid Intake Influences Phosphorus and Calcium Homeostasis in Preterm Infants – It Is Time to Change the Composition of the Early Parenteral Nutrition - Bonsante, Francesco; Iacobelli, Silvia; Latorre, Giuseppe; Rigo, Jacques; De Felice, Claudio; Robillard, Pierre Yves; Gouyon, Jean Bernard (PloS one, 2013)
Early aggressive parenteral nutrition (PN), consisting of caloric and nitrogen intake soon after birth, is currently proposed for the premature baby. Some electrolyte disturbances, such as hypophosphatemia and hypercalcemia, considered unusual in early life, were recently described while using this PN approach. We hypothesize that, due to its impact on cell metabolism, the initial amino acid (AA) amount may specifically influence the metabolism of phosphorus, and consequently of calcium. We aim to evaluate the influence of AA intake on calcium-phosphorus metabolism, and to create a calculation tool to estimate phosphorus needs. Prospective observational study. Phosphate and calcium plasma concentrations and calcium balance were evaluated daily during the first week of life in very preterm infants, and their relationship with nutrition was studied. For this purpose, infants were divided into three groups: high, medium and low AA intake (HAA, MAA, LAA). A calculation formula to assess phosphorus needs was elaborated, with a theoretical model based on AA and calcium intake, and the cumulative deficit of phosphate intake was estimated. 154 infants were included. Hypophosphatemia (12.5%) and hypercalcemia (9.8%) were more frequent in the HAA than in the MAA (4.6% and 4.8%) and in the LAA group (0% and 1.9%); both p<0.001. Calcium-phosphorus homeostasis was influenced by the early AA intake. We propose to consider phosphorus and calcium imbalances as being part of a syndrome, related to incomplete provision of nutrients after the abrupt discontinuation of the placental nutrition at birth (PI-ReFeeding syndrome). We provide a simple tool to calculate the optimal phosphate intake. The early introduction of AA in the PN soon after birth might be completed by an early intake of phosphorus, since AA and phosphorus are (along with potassium) the main determinants of cellular growth.